2020
DOI: 10.7883/yoken.jjid.2019.190
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Human β-Defensin 2 and the Vaginal Environment

Abstract: As one of the main antimicrobial peptides, human β-defensin 2 (HBD2) plays multiple roles in the lower genital tract. Based on the Nugent score as a diagnostic criterion for bacterial vaginosis, we sought to clarify the correlations among the Nugent score and Interleukin-6 (IL-6) and HBD2 levels in vaginal secretions in association with various types of infection. Ninety-eight women were recruited for this study. Levels of HBD2 and IL-6 in the vaginal wash were measured by enzyme-linked immunosorbent assays. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Women in early pregnancy who suffer from bacterial vaginosis have significantly lower hBD-2 concentrations in vaginal samples compared to healthy women [ 113 ]. In contrast, increased secretion of hBD-2 by the human vaginal epithelial cell line (VK2/E6E7) after stimulation with Candida albicans was described in in vitro studies [ 121 ]. In studies of the amniotic fluid, hBD-2 was present in all samples, but its concentration increased significantly during intra-amniotic infections [ 114 ].…”
Section: Hbd-2 In Pregnancy and Infancymentioning
confidence: 99%
“…Women in early pregnancy who suffer from bacterial vaginosis have significantly lower hBD-2 concentrations in vaginal samples compared to healthy women [ 113 ]. In contrast, increased secretion of hBD-2 by the human vaginal epithelial cell line (VK2/E6E7) after stimulation with Candida albicans was described in in vitro studies [ 121 ]. In studies of the amniotic fluid, hBD-2 was present in all samples, but its concentration increased significantly during intra-amniotic infections [ 114 ].…”
Section: Hbd-2 In Pregnancy and Infancymentioning
confidence: 99%
“…The association between hBDs and BV in reproductive-aged women has been poorly studied to date, and most of them are based on a very limited sample size [ 18 , 28 ]. Our study included a total of 634 measured samples and showed that BV has lower levels of hBD-1, -2 and -3.…”
Section: Discussionmentioning
confidence: 99%
“…crispatus in cervicovaginal lavage samples from healthy women. Accordingly, Kotani et al [ 18 ] reported the Nugent score for Lactobacillus morphotype point was well correlated with hBD-2. Additionally, studies using intestinal epithelial cell cultures demonstrate that Lactobacillus spp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…C. albicans responds to HBD-2 and HBD-3, executing a response to osmotic stress by activating the high-osmolarity glycerol (HOG) pathway [ 41 ]. The quantity of HBD-2 in the presence of C. albicans is augmented in the lower genital tract of women [ 42 ]. In addition, the presence of HBD-2 and HBD-3 is correlated with a better protection of the gut during C. albicans infections, as they promote the creation of tight junctions between the epithelial cells of the intestinal mucosa [ 43 ].…”
Section: Antimicrobial Peptides From Humansmentioning
confidence: 99%